Investigating Southeast Asian biomass burning by the WRF-CMAQ two-way coupled model: Emission and direct aerosol radiative effects. (1st February 2023) - Huang, Yeqi; Lu, Xingcheng; Fung, Jimmy C.H.; Wong, David C.; Li, Zhenning; Chen, Yiang; Chen, Wanying
Abstract: Southeast Asia (SEA) is one of the world's major sources of biomass burning (BB). In this study, the recently released Weather Research and Forecasting-Community Multiscale Air Quality (WRF-CMAQ) two-way coupled model was used with the Global Fire Emissions Database Version 4, to investigate the effect of BB emissions on the meteorology and air quality over SEA in March and April 2015. The results show that the model performance was improved by considering BB emissions. When BB pollutants reach the free troposphere, they can be transported by westerly and southwesterly winds to downstream regions. The contributions of BB were up to 48.4 and 35.5 ppbv to surface O3 concentrations and 251.0 and 104.4 μg/m 3 to surface PM2.5 concentrations in March and April, respectively. The BB emission caused aerosol direct radiative effect (DRE) on the monthly mean clear-sky downward shortwave flux at the ground surface to decrease by −65.4 and −33.6 W/m 2 in March and April, respectively. The surface temperature decreased over the land (by a maximum of −0.24 °C in March) and increased over the sea, while the temperature at higher levels tended to increase (to a maximum of 0.12 °C in March). The BB aerosol DRE caused the planetary boundary layer height (PBLH) to decrease by a maximum of −91.2 m in March. Surface O3 concentrations decreased generally owing to variations in the shortwave flux and temperature. Moreover, the decreased PBLH worsened the diffusion condition within the PBL but also caused larger amounts of BB emissions to penetrate the free atmosphere. This led to a decrease in surface PM2.5 concentrations in southern Indochina and an increase in Myanmar. These findings highlight the key effects of BB emissions on local and downwind meteorology and air quality over SEA and demonstrate the practical applications of the WRF-CMAQ coupled model. Highlights: The BB contributed up to 48.4 and 35.5 ppbv to O3 and 251.0 and 104.4 μg/m 3 to PM2.5 in March and April, respectively. The BB aerosol DRE caused ground downward shortwave to decrease by −65.4 and −33.6 W/m 2 in March and April, respectively. The surface temperature decreased over the land, while the temperature at higher levels increased due to aerosol DRE. The BB aerosol DRE caused the PBLH to decrease by a maximum of −91.2 m in March. The surface O3 decreased by −1.7 ppbv, and the surface PM2.5 varied within −6.6−18.5 μg/m 3 in March due to BB aerosol DRE.